Forming Process Analysis of an AA6060 Aluminum Vessel (Fracture and Structural Integrity, 2018)
This work analyses the results of a simple forming process of an AA6060 aluminium alloy sheet in order to validate the development of a simulation model based on the finite element method (FEM). This work represents the starting point of a broader study aimed at analysing the sheet formability. The FEM based model and the use of both the flow stress curve and the formability limit curve (FLC) were validated through the simulation of a simple forming process that required use of a hemispherical punch. The detailed analysis of the machining process by using FEM allows significant time and cost savings, avoiding "trial-and-error" operations that are normally used in the setup phase of the production process.
Keywords: AA6060 aluminium alloy; Forming process; Finite element method; Formability limit curve